Principle of a low-frequency transient electromagnetic radar system and its application in the detection of underground pipelines and voids. (April 2022) - Ye, Zijian; Zhang, Chengping; Ye, Ying
Highlights: A new method for detecting underground pipelines and voids was proposed. A transient electromagnetic radar (TER) system was developed. Variations of apparent resistivity of pipes with different materials were studied. Application effect of TER was studied. Abstract: The road collapse caused by tunnel construction was highly related to the leakage of the underground pipeline and the presence of voids. Thus, underground pipelines and voids should be clearly surveyed to prevent road collapse accident. The transient electromagnetic radar (TER) was developed and applied to the detection of underground pipeline and voids in this study. Variation of apparent resistivity in different materials underground pipelines were studied and summarized by the validation test. The application effect of TER in the inspection and recognition of different pipelines was verified by urban road detection before the subway station construction. Meanwhile, the application effect of TER in the detection of voids and loose soil area under the urban road subgrade was explored and analyzed in an urban road. The results show that: (i) different pipeline could be detected and distinguished by the variation of apparent resistivity; (ii) information of position, depth, size, and material of the underground pipelines and pipe trench could be discovered and located by TER; (iii) due to the difference of apparent resistivity, voids and loose soil area under the subgrade of the road could be detected and located by abnormal reflection signal of the lower apparent resistivity by TER. Thus, to prevent the road collapse effectively, the research and development of TER in the urban road detection provided a new idea for the inspection of underground pipeline and voids.